Global, regional, and national burden of neonatal otitis media attributable to PM2.5 air pollution: findings from the Global Burden of Disease study 2021 - Gong, Xin; Xu, Yinxia; Tu, Yuxi; Yuan, Chao; Zheng, Zhenhong; Song, Faling; Rao, Mengyu; Liu, Yan; Wang, Deping (Frontiers in Public Health, 2025)
BackgroundLong-term exposure to fine particulate matter (PM2.5) may increase the risk of otitis media (OM) in neonates. However, the global burden of neonatal OM attributable to PM2.5 remains poorly understood. This study aims to assess the burden and epidemiological trends in neonatal OM (0–28 days old) attributable to PM2.5 from 1990 to 2021.MethodsUsing data from the Global Burden of Disease (GBD) study 2021, we estimated the number and rates of disability-adjusted life years (DALYs) and years lived with disability (YLDs) associated with PM2.5-related OM in neonates. This analysis was stratified by sex, sociodemographic index (SDI), region, and country. The estimated annual percentage change (EAPC) method was used to assess temporal trends. Decomposition analysis was conducted to identify the main drivers of change.ResultsGlobally, the burden of neonatal OM attributable to PM2.5 levels declined from 1,363.136 DALYs (95% uncertainty interval [UI]: 512.175–2,946.844) in 1990 to 327.396 DALYs (95% UI: 156.269–626.363) in 2021. YLDs also decreased from 178.925 (95% UI: 82.305–314.825) to 165.301 (95% UI: 75.609–314.563). The burden of neonatal OM attributable to PM2.5 levels varied substantially across countries and regions, with higher numbers and rates of DALYs and YLDs in less-developed areas, where household PM2.5 pollution continues to play a crucial role. Decomposition analysis showed that epidemiological changes were the primary drivers behind the global decline in DALYs and YLDs, while population aging contributed to the increasing burden in low SDI regions.ConclusionAlthough the global burden of neonatal OM attributable to PM2.5 exposure has declined over the past three decades, it remains a persistent issue, particularly in resource-limited settings. Targeted interventions to reduce PM2.5 exposure—especially from household sources—are urgently needed to address these health disparities.